AKIBAT PRAKTIK KONGLOMERASI MEDIA PADA DEMOKRASI NEGARA DI ERA REVOLUSI - Fadillah, Siti Nurul (Fakultas Dakwah dan Komunikasi Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Abstract: In a democratic country, especially Indonesia, every citizen chooses the right to obtain and convey true, accurate and objective information regarding the democratic values ​​he conveys in Indonesia. This is where Indonesia defines information as “democratic oxygen” to achieve an open, free, correct, and objective government towards its people. The rationale is now that the media industry has grown into a business field that is oriented towards profit earned, to meet the needs and interests of the public in both contemporary and modern ways with the help of increasingly sophisticated technology in this revolutionary era with the phenomenon of the rise of media conglomeration. The method used in compiling this paper is a literature study by collecting data through documentation, library sources, and problem findings that refer to several sources. So it was found that the media in the revolutionary era, which was supposed to be a milestone in achieving the nation's democratic consolidation, was faced with the reality of the development of the media industry which shifted its function from social control of society to become a domain that promoted the interests of media ownership to achieve political interests.